South Qatar Survey Project, Katar: Archäologische Surveys in der südlichen Landeshälfte Katars - Pfeiffer, Kristina (e-Forschungsberichte des DAI, 2023)
The first project phase of the joint Qatari-German South Qatar Survey was carried out between 2012 and 2015 and focused on the study of long-term historical development of southern Qatar. The research concentrated on the systematic documentation of heritage sites. A total of 799 sites have been recorded so far by a comprehensive survey of geo-archaeologically significant regions, a survey of endangered places and already known places. The fieldwork was divided into several projects, such as a General Survey covering heritage sites and especially wells; the Asaila Survey which covered Qatar-B Neolithic sites and a Cairn Survey. The archaeological research is supplemented by interdisciplinary palaeo-environmental and geomorphological studies.